(OUT OF) CONTROL : 7th international biennial of photography and visual arts. - Barel, Lucien; Lesuisse, Anne-Françoise; Biennale van fotografie en visuele kunsten Luik 2010 (Luik : [s.n.], 2010)
Ader, Bas Jan ; Ballen, Roger ; Baker, Nathan ; Balcou, Béatrice ; Baudoux, Laura ; Berhtier, Julien ; Bertillon, Alphonse ; Bertin, Laure ; Bick, Nico ; Binschtock, Viktoria ; et al.
(OUT OF) CONTROL, verschillende locaties, Luik, Aachen, Eupen, Hasselt, Heerlen, Sittard, 28.02 - 25.04.2010
kunstcatalogus